Study on the Marsilea crenata extract supplementation on caudal epididymal plasma (CEP-3) to the Boer semen quality during cold storage - Wahjuningsih, Sri; Wulandari, Desinta (Faculty of Animal Science, Universitas Brawijaya, 2019)
The success of artificial insemination (AI) would be determined by the semen quality during storage. This research aims to evaluate the quality of Boer goat liquid semen stored with caudal epididymal plasma (CEP-3) supplemented with water clover (Marsilea crenata) extract or WCE during cold storage (3-5ºC). The semen was collected from Boer goat aged 2.5 to 3 years old by using an artificial vagina. The semen with >2+ mass motility and >70% individual motility were then selected for the study. A randomized block design which consisted of four treatments with ten replications as follow: P0 or control (CEP-3 + 10% egg yolk + 0.4% albumen); P1 (CEP-3 + 10% egg yolk + 0.4% albumen + 1% WCE; P2 (CEP-3 + 10% egg yolk + 0.4% albumen + 2% WCE); P3 (CEP-3 + 10% egg yolk + 0.4% albumen + 3% WCE) was used in this study. The data were analyzed with ANOVA and followed with Duncan’s multiple range test to determine significant differences. The results of this study showed that motility, viability, and membrane integrity in all treatments showed highly significant differences (P<0.01), while no significant difference (P>0.05) was shown on the semen abnormality. The result concludes that 1% WCE supplementation to the CEP-3 extender showed the best Boer semen quality during 96-hours cold storage.